Effects of Different Water Storage and Fertilizer Retention Substrates on Growth, Yield and Quality of Strawberry - Tang, Xiaofei; Li, Yonghui; Fang, Mengying; Li, Wei; Hong, Yong; Li, Yucheng (Agronomy (Basel), 2024)
To address the problems of inadequate water and fertilizer retention performance of the substrate, which results in the waste of water and fertilizer resources and then contributes to existing agricultural non-point source pollution, this study selected raw materials with different water retention performances for substrate compounding and explored their water retention performance and impact on the growth, yield and quality of strawberries. The experimental setup utilized the strawberry cultivar ‘Hongyan’ as the test subject and incorporated different proportions of vermicompost, coconut bran, biochar and humic acid into the organic fertilizer. A total of 12 treatment groups were formed across three gradients, involving different proportions of vermicompost with 0.05, 0.10 and 0.15 proportions of coconut bran/biochar and 0.05, 0.15 and 0.20 proportions of humic acid. To evaluate the water retention performance, uniform water and fertilizer regulations were applied. The results revealed that the treatment groups T4 (vermicompost:coconut bran = 0.5:0.1) and T5 (vermicompost:biochar = 0.5:0.1) exhibited higher water absorption multiplicity, lower water infiltration rates, and better water retention performances, but there was no significant difference between the two treatment groups. Among them, T4 could effectively improve the nutrient content of the substrate, and the substrate nitrogen-use efficiency (NUE) increased by 5.80% compared with CK2. Also, plant total nitrogen (TN) and total phosphorus (TP) uptake increased by 81.18% and 4.74%, respectively, compared with CK2, which in turn promoted the growth and development of the plant and improved the fruit yield and quality to a certain extent. Meanwhile, T4 had the highest urease and catalase activities, with sucrase activity ranking second only to T1. In contrast, T5 demonstrated greater effectiveness in improving the average fruit weight and maximum fruit weight, registering increases of 22.98% and 36.22% compared to CK2, respectively, but the effect on the total yield was less pronounced. A comprehensive evaluation of strawberry growth found that the T4 treatment was superior. In conclusion, the ratio of vermicompost and coconut bran at 0.5:0.1 improved and promoted the substrate water retention performance and strawberry growth.